PENGARUH HARGA, VOLATILITAS RETURN, DAN VOLUME TRANSAKSI SAHAM TERHADAP LIKUIDITAS SAHAM - Cici Widowati (JBIMA (Jurnal Bisnis dan Manajemen), 2013)
The focus of this study is to investigate the relationship between stocks’ trading characteristics (stock price, return volatility, and transaction volume) and stock liquidity. This study uses 5 liquidity proxies: relative bid-ask spread, stock turnover, illiquidity ratio, zero return measure, and turnover-adjusted number of zero daily volume. By using the correlation matrix, this study shows that there is a consistent relationship among the liquidity proxy. It means that liquid stock has high stock turnover, low relative bid-ask spread, low illiquidity ratio, low zero return measure, and low turnover-adjusted number of zero daily volume.The analysis in this paper uses 108 sample of listed company in Indonesia Stock Exchange (IDX), which is carried out at the monthly level from January 2006 to the end of December 2010. The samples in this paper are allocated into three groups: small firms, medium firms, and large firms. The regression analysis is estimated to all sample, small firms’ sample, medium firms’ sample, and large firms’ sample.The results indicate that the influence of stock transaction volume on liquidity is always consistent and significantly positive. However, some proxies do react differently to the stock price and return volatility. According to the results of this paper, the influence of stock price on liquidity is always significantly positive since the liquidity proxy is the illiquidity ratio, zero return measure, or turnover-adjusted number of zero daily volume. But, the influence of return volatility on liquidity is always significantly negative since the liquidity proxy is the relative bid-ask spread, or illiquidity ratio. This result also indicates that illiquidity ratio always reacts consistently to the stock price, return volatility, and transaction volume.